2015
DOI: 10.1039/c5tc01624j
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic enhancement of organic solar cell thermal stability by wire bar coating and light processing

Abstract: † Electronic Supplementary Information (ESI) available: SC and WBC drying kinetics measurements. UV-vis absorption spectra of SC and WBC PCDTBT:PC60BM blend layers. PL spectra of SC and WBC blended layers and their respective PCDTBT neat layers. EQE of blend devices deposited by SC and WBC techniques. Optical microscopy images of the blend layer deposited by SC and WBC on SiOx (as cast) and PEDOT:PSS (at 80°C and 140°C thermal annealing temperature). SeeWe demonstrate that organic solar cells can exhibit diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The morphological stability of polymer/fullerene solar cells to thermal stresses and light exposure was investigated with model PS:PCBM thin films. Our work builds upon numerous reports of C 60 and PCBM phototransformations, dimerization, and burn‐in effects in organic solar cell stability, by our group and several others . To the best of our knowledge, however, this is the first time that the coupling of illumination, known to induce fullerene dimerization, and thermal stress, known to induce decomposition (or dedimerization), were simultaneous investigated.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The morphological stability of polymer/fullerene solar cells to thermal stresses and light exposure was investigated with model PS:PCBM thin films. Our work builds upon numerous reports of C 60 and PCBM phototransformations, dimerization, and burn‐in effects in organic solar cell stability, by our group and several others . To the best of our knowledge, however, this is the first time that the coupling of illumination, known to induce fullerene dimerization, and thermal stress, known to induce decomposition (or dedimerization), were simultaneous investigated.…”
Section: Discussionmentioning
confidence: 81%
“…This stabilization effect was also observed upon addition of chemically (rather than photochemically) synthesized fullerene dimers, which is likely related to the combined frustration of the fullerene crystallization processes and their reduced mobility. Substrate segregation and deposition methods, combined with light exposure, were found to synergetically prolong the lifetime of PCDTBT:PC 60 BM in excess of 200 times, compared to a reference device. However, other reports suggest detrimental or neutral effects to PCE upon illumination.…”
Section: Introductionmentioning
confidence: 99%
“…8,97 The versatile morphological stabilisation observations hold for other polymer:C 60 and polymer:PC 61 BM systems; 8,30,94,95 other substrates; 8,97 and other deposition methods. 98 While fullerene dimerisation is general to many donor polymers and has a significant impact on their thermal stability, the photoinduced fullerene dimers can be thermally reversed to its pristine monomeric form especially at sufficiently elevated temperatures, see Fig. 5(c).…”
Section: Morphological Stability Under Thermal Stressmentioning
confidence: 99%
“…51 Whilst wire-bar coating can affect vertical phase separation and film nucleation, likely correlated with the increased drying times, and can lead to improved stabilities when compared to spin-coated devices. 98 The interaction between interlayers and the active layer can also affect morphological stability, for example, by controlling the nucleation and film formation processes, 97 and the driving force for vertical phase separation. 160 Selection of a better matched interlayer can effectively address these issues.…”
Section: Solvents and Processingmentioning
confidence: 99%
“…The importance of the drying pathway has been recognised by several authors and has been found to considerably impact performances. [22][23][24]…”
Section: Annealing Protocolsmentioning
confidence: 99%